Adolescent romantic relationships as a tug of war: The interplay of power imbalance and relationship duration in adolescent dating aggression. Issue 6 (22nd July 2020) - Cuccì, Gaia; Confalonieri, Emanuela; Olivari, Maria Giulia; Borroni, Elisa; Davila, Joanne
Abstract: The present study investigates the link between power imbalance within the romantic couple and psychological, relational and physical adolescent dating aggression (ADA) perpetration, considering also the role of relationship duration as an indicator of the developmental stage of the relationship. This is the first investigation into whom is perceived to have power in the relationship (the partner or the subject him/herself) by distinguishing between male and female adolescents. Participants were 805 Italian adolescents (36.1% males; 63.9% females) aged 14–20 years ( M age  = 17.16 years, SD age  = 1.34), all reporting having been in a romantic relationship currently or within the past 6 months. Males perceiving a balanced relationship reported lower levels of psychological ADA perpetration, and they perpetrated more relational ADA in longer relationships where the partner is perceived to have the power. No significant findings emerged regarding physical ADA. Females perceiving themselves as having the power in the relationship reported higher levels of psychological and physical ADA perpetration. They perpetrated more relational ADA when they perceived the partner as having the power in the relationship. Also, females in longer relationships in which power was not perceived as equally shared between partners reported higher physical ADA perpetration. Finally, for both males and females, longer relationships were characterized by higher levels of ADA toward the partner. Findings highlight the importance of studying the interplay between power imbalance and relationship duration on ADA perpetration, and provide the way to understand possible functions of ADA within a romantic relationship.